2014
DOI: 10.1007/s12026-014-8578-0
|View full text |Cite|
|
Sign up to set email alerts
|

Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I

Abstract: The pathogenicity of antibodies against β2-glycoprotein I (anti-β2GPI) depends on multiple factors such as subclass type, epitope binding and avidity. Due to their large heterogeneity, their impact on antiphospholipid syndrome (APS) onset is still not fully clarified. We studied the binding characteristics of IgG anti-β2GPI with known avidity from sera of 201 autoimmune patients (87 with APS, 67 with APS associated with systemic lupus erythematosus (SLE), 47 with only SLE) to six β2GPI peptides corresponding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…It is thus not surprising if the most recent studies have further confirmed the role of antidomain I antibody positivity as a strong predictor of thrombotic events and, to a lesser extent, of pregnancy complications. Noteworthy, up to onethird of patients carrying anti-b2GPI antibodies were negative for anti-domain I IgG [7 && ,8]; the observation that a consistent rate of APS patients display autoantibodies reacting with b2GPI epitopes other than domain I was confirmed in a multicentre study [9] using several peptides spanning the different domains of the molecule.…”
Section: Anti-b2gpi Domain I Antibodiesmentioning
confidence: 99%
“…It is thus not surprising if the most recent studies have further confirmed the role of antidomain I antibody positivity as a strong predictor of thrombotic events and, to a lesser extent, of pregnancy complications. Noteworthy, up to onethird of patients carrying anti-b2GPI antibodies were negative for anti-domain I IgG [7 && ,8]; the observation that a consistent rate of APS patients display autoantibodies reacting with b2GPI epitopes other than domain I was confirmed in a multicentre study [9] using several peptides spanning the different domains of the molecule.…”
Section: Anti-b2gpi Domain I Antibodiesmentioning
confidence: 99%
“…Thus anti‐DI‐β2GPI autoantibodies confer LA activity associated with the highest risk of thrombosis (de Laat et al , ), frequently present in triple aPL‐positive patients, are closely associated with both thrombosis and pregnancy loss (de Laat et al , ) and increase thrombus size in mouse models (Pericleous et al , ). Of note, about 30% of patients with anti‐β 2 GPI antibodies are negative for anti‐DI–β 2 GPI antibodies (Pengo et al , ) and the clinical significance of autoantibodies reacting with epitopes other than DI was investigated in a multicentre study (Artenjak et al , ). This study analysed serum samples from 201 autoimmune patients with IgG anti‐ β2GPI activity (87 APS, 67 APS plus SLE and 47 with SLE only) for their binding to six β2GPI peptides corresponding to amino acid clusters on domains I‐II, II, III and III‐IV.…”
Section: Pathogenesis Of Antiphospholipid Syndromementioning
confidence: 99%
“…48,61 Inconsistently, another study did not find a significant association between antidomain I IgA antibodies and thrombosis. 66 Looking at the titers of antidomain I antibodies, de Craemer et al demonstrated significantly reduced levels in clinically unaffected patients. 54 Antidomain I antibodies proved to be highly prevalent in patients with a history of thrombosis, whereas antibodies targeting other domains were shown in patients with and without thrombosis.…”
Section: Detection Of Domain I Antibodiesmentioning
confidence: 99%
“…Nonetheless, most studies agree that a significant proportion of patients positive for antiβ 2 GPI antibodies are negative for antidomain I antibodies, and the existence of autoantibodies reacting with nondomain I epitopes has been demonstrated. 53,57,66 As a result, to avoid false-negative results, replacement of available full-length anti-β 2 GPI assays with specific antidomain I assays may not be advised at this stage. Nevertheless, sideby-side application may improve risk stratification of clinical events.…”
Section: Detection Of Domain I Antibodiesmentioning
confidence: 99%